Implementasi Kebijakan Kartu Identitas Anak (KIA) di Kabupaten Bintan Tahun 2024 - Eka Nurtiara; Afrizal Afrizal; Ella Afnira (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2025)
The Child Identity Card (KIA) is an official document issued to children aged 0–17 years as a form of early recognition and protection of legal identity. The issuance of the KIA aims to support orderly population administration, facilitate access to public services, and strengthen child protection in various social, educational, and health aspects. In Bintan Regency, this policy has been implemented since 2017 and was reinforced through Regent Regulation No. 6 of 2022. However, in 2024, the KIA ownership rate only reached 53.48%, the lowest figure in the Riau Islands Province. This figure indicates a serious gap between policy and implementation in the field. In fact, the Bintan Regency Population and Civil Registration Office's Work Plan (Renja) set the KIA ownership target for 2024 at 65%, with the final realization being only 62%. This study aims to examine the factors influencing the low KIA ownership rate. The study used a descriptive qualitative approach with data collection techniques through in-depth interviews, observation, and documentation. Informants consisted of Disdukcapil officials and the community as service recipients. The implementation model used was Merilee S. Grindle's theory, which emphasizes six critical variables in policy success, including resources, communication, and implementer characteristics. The results of the study indicate that despite an increase in demand for KIA due to administrative requirements in education services, BPJS, and social programs, significant obstacles remain. These obstacles include limited outreach, a lack of service infrastructure in coastal and remote areas, and technical constraints such as a suboptimal online system. Therefore, acceleration strategies are needed, such as increasing the intensity of cross-sector outreach, integrating KIA services into integrated health post (Posyandu) and school programs, adding mobile services, and training local human resources.